Analisis Yuridis terhadap Tindak Pidana Penggelapan Dalam Jabatan yang dilakukan Secara Berlanjut - Ida Bagus Gede Arimbawa Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
In Indonesia, there is a classification of criminal acts that occur in social life, one of which is the crime of embezzlement committed by someone who is in a certain agency by using his position. This crime is closely related to morals and belief in someone's honesty which leads to a lie about that belief that takes advantage of the position itself. This research aims to determine the legal regulation of the crime of embezzlement in office, and to know the law enforcement against the perpetrators of the crime of embezzlement in office in Decision Number 58/pid.B/2021/PN Gin. This research uses normative research type. Sources of legal materials consist of primary, secondary and tertiary with statutory and conceptual approaches. Data were collected by recording and documenting, and analyzed descriptively analytically. The criminal act of embezzlement in office is continuously regulated in articles 372 to 376 of the Criminal Code. In Article 374 of the Criminal Code, the perpetrator is threatened with a maximum imprisonment of 5 (five) years. Meanwhile, criminal acts are continuously regulated in Article 64 paragraph (1), the perpetrators can be punished. And according to Decision No. 58/Pid.B/2021/PN.Gin, the perpetrator was sentenced to prison for 3 (three) years and charged him with paying court fees in the amount of IDR 5,000 (five thousand rupiah).